BENTUK PENCEGAHAN TERHADAP INDIKASI PRAKTEK PREDATORY PRICING OLEH SELLER ASING DI E-COMERCE - Nouvia Noor Maulidya M. (2022)
The development of the world of trade and the ease of transactions provided by e-commerce provide opportunities for business actors to expand the market as wide as possible. Foreign business actors can sell their products to other countries without having to be present in the country concerned or what is called a cross-border transaction. Domestic business actors and foreign business actors compete with each other to provide the lowest possible prices to attract consumers. The existence of foreign business actors who price their products at very low prices in e-commerce gives rise to indications of predatory pricing practices. The problem that the author will raise is how to enforce the law against indications of predatory pricing practices by foreign sellers in e-commerce and how to indicate predatory pricing practices by foreign sellers in e-commerce. This writing uses a normative juridical method. predatory pricing or the practice of selling at a loss is regulated in Article 20 of Law no. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Proof of the practice of selling at a loss is carried out using a rule of reason approach where action can only be taken if it is proven to have a negative impact on business competition practices. However, Indonesia does not yet have comprehensive regulations regarding predatory pricing and other anti-competitive practices by foreign business actors in e-commerce. The giving of low prices or the practice of selling at a loss by foreign sellers in e-commerce does not violate Article 20 of Law no. 5 of 1999 if it is not intended to inhibit and kill business competitors in the relevant market and aims to increase prices in the future with the hope of gaining profits and covering losses that have been suffered in the beginning and caused losses to consumers.